2014
DOI: 10.1371/journal.pone.0086077
|View full text |Cite
|
Sign up to set email alerts
|

Association between the IL1B (-511), IL1B (+3954), IL1RN (VNTR) Polymorphisms and Graves' Disease Risk: A Meta-Analysis of 11 Case-Control Studies

Abstract: BackgroundData on the association between the interleukin-1 (IL-1) gene polymorphisms and Graves' disease (GD) risk were conflicting. A meta-analysis was undertaken to assess this association.MethodsWe searched for case-control studies investigating the association between the IL1B (-511), IL1B (+3954), IL1RN (VNTR) polymorphisms and GD risk. We extracted data using standardized forms and calculated odds ratios (OR) with 95% confidence intervals (CI).ResultsA total of 11 case-control studies were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…As a potent proinflammatory cytokine, IL-1β plays an important role in many inflammation-related diseases as well as cancer. Accordingly, IL1B gene polymorphisms, especially functional SNPs -31 T>C (rs1143627) and -511 G>A (rs16944) are associated with susceptibility to a number of diseases [11] , [12] , [13] , [14] . IL-1β is also important in the pathogenesis of TB in mice [15] , and polymorphisms in the human IL1B gene have been suggested to have differing effects on TB susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…As a potent proinflammatory cytokine, IL-1β plays an important role in many inflammation-related diseases as well as cancer. Accordingly, IL1B gene polymorphisms, especially functional SNPs -31 T>C (rs1143627) and -511 G>A (rs16944) are associated with susceptibility to a number of diseases [11] , [12] , [13] , [14] . IL-1β is also important in the pathogenesis of TB in mice [15] , and polymorphisms in the human IL1B gene have been suggested to have differing effects on TB susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study has proved that increasing the levels of TNF-α and IL-1β correlated with GD. In addition, IL-1β induces production of hyaluronan by primary thyroid epithelial cells and thyroid fibroblasts, a process that may contribute to the development of goiter in GD [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β also enhances T cell-dependent antibody production by augmenting CD40 ligand and OX40 expression on T-cells. IL-1β was shown to promote differentiation of T-helper 17 (Th17) cell, the proportion of which was reported to be higher in intractable GD than that of GD in remission [15]. In fact, patients with autoimmune diseases, such as systemic lupus erythematosus (SLE), have reduced TGF-β production in their peripheral blood cell cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of 37 studies Ying recently reported that IL-1β-31C>T polymorphism might confer susceptibility to gastric cancer in the presence of H.pylori infection, indicating gene-environment interaction in gastric carcinogenesis (82). Another analysis of 11 case-control studies by Chen et al confirmed significant protection of the IL-1b-511C>T polymorphism from Grave's Disease in Asians, but not in Caucasians (15). These results may indicate that the pancreatitis risk evaluation of IL polymorphisms is more complex than previously thought and future studies should be carefully designed to consider genetic background differences, as well as additional geneenvironment interactions.…”
Section: Disease Severity and Prognostic Markermentioning
confidence: 99%